SLC2A1 and MPST as diagnostic and prognostic biomarkers of potential endometrial cancer - Xi, Xiaoyu; Gong, Xinxin; Liu, Yixi; Cui, Boran; Xia, Chenchen; Qin, Shan; Du, Jiexian (Frontiers in Immunology, 2025)
Uterine corpus endometrial carcinoma (UCEC) is the predominant neoplasm affecting the female reproductive system. Early diagnosis of UCEC is crucial for improving patient survival rates. In this study, we selected and investigated two specific genes associated with hydrogen sulfide(H2S): SLC2A1, which encodes a glucose transporter, and MPST, which encodes 3-mercaptopyruvate thiotransferase. Both SLC2A1 and MPST have been identified as important regulators in cancer. The objective of this study was to investigate the potential significance of SLC2A1 and MPST in terms of UCEC diagnosis and prognosis. Our analysis using Kaplan-Meier survival curves and receiver operating characteristic (ROC) curves demonstrated robust diagnostic and prognostic significance for both SLC2A1 and MPST. Moreover, our research revealed a significant association between the expression levels of SLC2A1 and MPST, immune cell infiltration, immune checkpoint gene presence, and TP53 in UCEC tissues. Furthermore, we observed that DNA methylation status of the CpG island of SLC2A1 and the MPST gene is associated with UCEC prognosis. These findings suggest that SLC2A1 and MPST genes hold promise in distinguishing endometrial cancer patients from normal cases, highlighting their diagnostic and prognostic potential as biomarkers for UCEC. These results offer encouraging prospects for targeted therapies.